Ten Fundamental Questions for Water Resources Development in the Ganges : Myths and Realities - Sadoff, Claudia; Harshadeep, Nagaraja Rao; Blackmore, Donald J.; Wu, Xun; O'Donnell, Anna; Jeuland, Marc; Lee, Sylvia; Whittington, Dale (IWA Publishing, 2016)
This paper summarizes the results of the Ganges Strategic Basin Assessment (SBA), a 3-year, multi-disciplinary effort undertaken by a World Bank team in cooperation with several leading regional research institutions in South Asia. It begins to fill a crucial knowledge gap, providing an initial integrated systems perspective on the major water resources planning issues facing the Ganges basin today, including some of the most important infrastructure options that have been proposed for future development. The SBA developed a set of hydrological and economic models for the Ganges system, using modern data sources and modeling techniques to assess the impact of existing and potential new hydraulic structures on flooding, hydropower, low flows, water quality and irrigation supplies at the basin scale. It also involved repeated exchanges with policymakers and opinion makers in the basin, during which perceptions of the basin could be discussed and examined. The study’s findings highlight the scale and complexity of the Ganges basin. In particular, they refute the broadly held view that upstream water storage, such as reservoirs in Nepal, can fully control basin wide flooding. In addition, the findings suggest that such dams could potentially double low flows in the dry months. The value of doing so, however, is surprisingly unclear and similar storage volumes could likely be attained through better groundwater management. Hydropower development and trade are confirmed to hold real promise (subject to rigorous project level assessment with particular attention to sediment and seismic risks) and, in the near to medium term, create few significant tradeoffs among competing water uses. Significant uncertainties, including climate change, persist, and better data would allow the models and their results to be further refined.